The joy of Mathematica : - Schuchat, Alan (Harcourt Academic, 2000)
Joy of Mathematica, Second Edition, is a book and software combination for Windows and Macintosh that makes Mathematica easier to use and learn. The software includes the most common Mathematica operations needed in the first two years of college and university courses. The book is a manual for the software and an introduction to using Mathematica for mathematics and its applications to other fields. It contains material for students in calculus, differential equations, and linear algebra courses. Students and professionals will benefit from this user-friendly, practical guide to Mathematica.